Combined Method to Remove Endotoxins from Protein Nanocages for Drug Delivery Applications: The Case of Human Ferritin - Filippo Silva; Leopoldo Sitia; Raffaele Allevi; Arianna Bonizzi; Marta Sevieri; Carlo Morasso; Marta Truffi; Fabio Corsi; Serena Mazzucchelli (MDPI AG, 2021)
Protein nanocages represent an emerging candidate among nanoscaled delivery systems. Indeed, they display unique features that proved to be very interesting from the nanotechnological point of view such as uniform structure, stability in biological fluids, suitability for surface modification to insert targeting moieties and loading with different drugs and dyes. However, one of the main concerns regards the production as recombinant proteins in E. coli, which leads to a product with high endotoxin contamination, resulting in nanocage immunogenicity and pyrogenicity. Indeed, a main challenge in the development of protein-based nanoparticles is finding effective procedures to remove endotoxins without affecting protein stability, since every intravenous injectable formulation that should be assessed in preclinical and clinical phase studies should display endotoxins concentration below the admitted limit of 5 EU/kg. Different strategies could be employed to achieve such a result, either by using affinity chromatography or detergents. However, these strategies are not applicable to protein nanocages as such and require implementations. Here we propose a combined protocol to remove bacterial endotoxins from nanocages of human H-ferritin, which is one of the most studied and most promising protein-based drug delivery systems. This protocol couples the affinity purification with the Endotrap HD resin to a treatment with Triton X-114. Exploiting this protocol, we were able to obtain excellent levels of purity maintaining good protein recovery rates, without affecting nanocage interactions with target cells. Indeed, binding assay and confocal microscopy experiments confirm that purified H-ferritin retains its capability to specifically recognize cancer cells. This procedure allowed to obtain injectable formulations, which is preliminary to move to a clinical trial.